Kajian Literatur: Perkembangan Komunikasi CSR dan Reputasi Perusahaan - Subowo, Fahmi Hassan; Anshori, Mahfud (Universitas Sebelas Maret (UNS), 2025)
This study aims to review the literature on the relationship between Corporate Social Responsibility (CSR) communication and corporate reputation. The review analyzes over twenty international research papers published between 2019 and 2023. Findings indicate that CSR is not merely philanthropic activity but a strategic communication instrument crucial for shaping corporate image, trust, and long-term reputation. Theoretical frameworks such as the Stakeholder Theory, Resource-Based View (RBV), Social Identity Theory, and Signaling Theory have been widely applied. Effective CSR communication—through both traditional and digital media—has been shown to strengthen corporate reputation and foster emotional connections with stakeholders. The review concludes that a strong corporate reputation is built upon CSR practices communicated authentically, consistently, and sustainably.